Urgensi Pemimpin Sebagai Supervisor dalam Meningkatkan Profesionalisme Guru di SMAN 5 Payakumbuh - Fatma Sari; Junaidi Junaidi; Supriadi Supriadi; Susanda Febriani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Leaders should play a supervisory role in improving the professionalism of teachers. This is because the improvement in teacher professionalism should not only depend on government efforts, but also require the teacher himself to have a strong determination to become more professional. Only in this way can the goal of national education be fulfilled. Professional teachers must have expertise in various disciplines of science, teaching resources, instructional strategies, student motivation, and have advanced capabilities and broad knowledge in the field of education. The methods in this research are qualitative descriptive methods and the type of research of phenomena occurring in the field. The location of this research is in SMAN 5 Payakrasuh. The findings are that surveillance is carried out with the aim of developing and improving teaching skills in educational institutions. Supervision enhances the professional competence of teachers, enabling them to effectively implement the learning process in the classroom. In addition, teachers can fulfil their role as professional educators by effectively carrying out their duties and responsibilities in guidance and teaching, as well as creating a learning environment that supports and promotes effective communication.